2008
DOI: 10.3170/2008-8-18435
|View full text |Cite
|
Sign up to set email alerts
|

Improved quality of beneath‐canopy grass in South African savannas: Local and seasonal variation

Abstract: Questions: Do large trees improve the nutrient content and the structure of the grass layer in savannas? Does the magnitude of this improvement differ with locality (soil nutrients) and season (water availability)? Are grass structure and species composition beneath tree canopies influenced by soil fertility and season? Location: South Africa. Methods: We compared grass leaf nutrient contents and grass sward structure beneath and outside tree canopy areas in three savannas of different soil fertility during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
56
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 39 publications
3
56
0
1
Order By: Relevance
“…Grasses growing under the tree canopy contained more green leaf material and stayed green for longer into the dry season than grasses growing further away from trees (Treydte et al 2008). Overall, trees contribute substantially to the grass species layer and to vertical and horizontal structural diversity in African savannah systems.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations
“…Grasses growing under the tree canopy contained more green leaf material and stayed green for longer into the dry season than grasses growing further away from trees (Treydte et al 2008). Overall, trees contribute substantially to the grass species layer and to vertical and horizontal structural diversity in African savannah systems.…”
Section: Introductionmentioning
confidence: 97%
“…Trees can improve the conditions for grass layer growth directly, for example, by providing shade and reducing evapo-transpiration, by accumulating soil nutrients close to their root systems (Belsky 1994;Dean et al 1999), and by changing the micro-climate (Jackson et al 1990;Belsky 1994;Ludwig et al 2001;Power et al 2003). Recent studies have shown that both soil and grass nitrogen (N) and phosphorus (P) contents were elevated beneath tree canopies compared to inter-canopy sites (Ludwig et al 2004;Treydte et al 2007Treydte et al , 2008 whereas some studies did not find any or only slight differences in soil properties between canopy and inter-canopy sites (Witkowski and Garner 2000).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…They frequently clear most of the shrubs and trees inside the enclosures by leaving a few species, which are used to shade their animals from direct hot sun. A low density of woody species has been shown to increase soil nutrient status and thus encourage grass-growing conditions [55,56]. The overall density threshold of woody species in terms of bush encroachment is estimated to be more than 2500 trees equivalent ha -1 [57].…”
Section: Interaction Of Management and Vegetation Attributesmentioning
confidence: 99%